Mélanome acral du pied: a propos de 9 cas et revue de la littérature [Acral melanoma of the foot: a study of 9 cases and guidelines update] - Sid'Ahmed Mohamed Limam; Cheikh Elmoustapaha Erebih; Abdelaziz Beyrouk (Our Dermatology Online, 2019)
Background: Malignant Melanoma is a malignancy of pigmented-producing cells (melanocytes). Acral melanoma is located on non-hair bearing skin of palms and soles or under the nail bed. This histological subtype is often described in darker skin. Patients commonly display advanced stage of disease at presentation. This leads, inevitably, to poor disease prognosis. The functional requirement together with the wide excision in the foot makes treatment of melanomas a challenging for the surgeons. Methods: We retrospectively collected clinical, pathological, surgical and follow-up data of 12 acral melanoma cases in the foot. Three patients whose records contained insufficient information were excluded. Results: The mean age was 65 years (43-70years). 5 patients were female and 4 were male. The heel was the most commonly involved location with 50 % of the patients. Clark's Level showed advanced stages IV and V with more than 88, 88 % of the patients. Wide excision until the plantar fascia was performed in all patients (9 cases) and for metastatic sentinel nodes; complete lymphadenectomy was performed in 2cases. Lymphadenectomy of retroperitoneal nodes was made in 1 case; resection of crural metastasis was done in 2 cases. In Postoperative coverage: primary closure was feasible (n=2), skin graft (n=2) and spontaneous wound healing (n=5). Conclusion: Acral melanoma is the commonest melanoma in our practice. Most of the cases presented with advanced stage disease.